Difference in the topography of atherosclerosis in the left versus right coronary artery in patients referred for coronary angiography - Giannoglou, George D (BioMed Central, 2010)
BACKGROUND: We sought to determine the difference in the localization of coronary artery disease (CAD) between the left and right coronary artery system and investigate the effect of sex and age on that difference. METHODS: We retrospectively analyzed 17,323 consecutive angiographies from January 1(st), 1984 to December 31(st), 2003. The demographic parameters, in particular age and sex of the investigated cases as well as the angiographic results were recorded and summarized. RESULTS: Of 13,305 cases with CAD, 861 (6.5%) had right coronary artery (RCA)-only disease, 4,621 (34.7%) had left coronary artery (LCA)-only disease, while 7,823 (58.8%) cases had concomitant RCA and LCA disease. LCA-only disease was more frequent than RCA-only disease [LCA-only/RCA-only odds ratio (OR): 5.37, 95% CI: 4.99 to 5.77, p < 0.001]. Women were more likely to have LCA-only disease (men/women OR 0.75 95% CI: 0.68 to 0.82, p < 0.001) compared with men who were more likely to present with concomitant RCA and LCA disease (men/women OR 1.33 95% CI: 1.21 to 1.45, p < 0.001). RCA-only and LCA-only disease were both more frequent in patients aged from 51 to 60 years, while concomitant RCA and LCA disease in patients between 61 and 70 years of age. CONCLUSIONS: LCA-only disease is more frequent than RCA-only disease. Men have a higher probability than women to present with concomitant RCA and LCA disease while women are more likely than men to be found with LCA-only disease.